mDia1 and formins: screw cap of the actin filament - Mizuno, Hiroaki (Biophysics (Nagoya-shi), 2012)
Formin homology proteins (formins) are actin nucleation factors which remain bound to the growing barbed end and processively elongate actin filament (F-actin). Recently, we have demonstrated that a mammalian formin mDia1 rotates along the long-pitch helix of F-actin during processive elongation (helical rotation) by single-molecule fluorescence polarization. We have also shown processive depolymerization of mDia1-bound F-actin during which helical rotation was visualized. In the cell where F-actins are highly cross-linked, formins should rotate during filament elongation. Therefore, when formins are tightly anchored to cellular structures, formins may not elongate F-actin. Adversely, helical rotation of formins might affect the twist of F-actin. Formins could thus control actin elongation and regulate stability of cellular actin filaments through helical rotation. On the other hand, ADP-actin elongation at the mDia1-bound barbed end turned out to become decelerated by profilin, in marked contrast to its remarkably positive effect on mDia1-mediated ATP-actin elongation. This deceleration is caused by enhancement of the off-rate of ADP-actin. While mDia1 and profilin enhance the ADP-actin off-rate, they do not apparently increase the ADP-actin on-rate at the barbed end. These results imply that G-actin-bound ATP and its hydrolysis may be part of the acceleration mechanism of formin-mediated actin elongation.